Biocompatible PLGA-PCL nanobeads for efficient delivery of curcumin to lung cancer - Sheida Sadeghi; Javad Mohammadnejad; Akram Eidi; Hanieh Jafary (Cancer Nanotechnology, 2024)
Abstract Lung cancer has been mentioned as the first and second most prevalent cancer among males and females worldwide, respectively since conventional approaches do not have enough efficiency in its suppression. Therefore, a biocompatible and efficient polylactic-co-glycolic acid (PLGA: P)- poly-ε-caprolactone (PCL: P) copolymer was fabricated for delivery of relatively insoluble curcumin (Cur) to A549 lung cancer cells. Next, the physicochemical aspects of the synthesized nanobeads were characterized by applying analytical sets, including FT-IR, DLS, TEM, and TGA as nano-metric size (20–45 nm) and 1.29% of Cur entrapment efficiency were determined for P-P-Cur nano-beads. Thereafter, a controlled (5% within 2 h at pH 7.4) and pH-sensitive (nearly 50% within 4 h at pH 5.0) drug release manner was observed for P-P-Cur nanobeads. Thereafter, biomedical assays were conducted for the cancer suppression ability of nanobeads. 41% cell viability after 24 h of treatment with 200 nM concentration and 7.55% cell cycle arrest at 5 h of post-treatment with 100 nM (IC50) concentration were attained for P-P-Cur. Also, 7-fold increase and 2-fold decrease in the expressions of Caspase-9 (apoptotic gene) and Bcl2 (anti-apoptotic gene) were observed which have further approved the cancer inhibition potency of the P-P-Cur sample. The cellular uptake results indicated 91% internalization in A549 cells while it was less than 1% for the pure Cur. These data have demonstrated that P-P-Cur can use as a biocompatible drug delivery system for Cur and treatment of lung cancer.